Pass by, call in - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In Spore 94 we featured a cocoa poster, published by the Farming World Services, Box 294, Ikom, Cross River State, Nigeria; email: farmingworld2000@yahoo.com. The coordinator of FWS, Henry Ogar Etta, writes in to announce that 'Cross River State of...